2016
DOI: 10.1007/s00422-016-0680-z
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent linear damping characterization in linear and nonlinear force–stiffness muscle models

Abstract: In the current research, the muscle equivalent linear damping coefficient which is introduced as the force-velocity relation in a muscle model and the corresponding time constant are investigated. In order to reach this goal, a 1D skeletal muscle model was used. Two characterizations of this model using a linear force-stiffness relationship (Hill-type model) and a nonlinear one have been implemented. The OpenSim platform was used for verification of the model. The isometric activation has been used for the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The classic macroscopic Hill model, consisting of simple first order ordinary differential equations, is sufficient to simulate contracting muscle when considering hysteresis effects and has been firmly established as a reliable model of muscle contractile dynamics for many decades. A review of the developments of the Hill model up to 2016 can be found in [Ovesy, et al, 2016]. One of the major disadvantages of the Hilltype models is that the viscoelastic analogies do not map to the underlying physiological mechanisms associated with muscle.…”
Section: Results Of the Mathematical Modelmentioning
confidence: 99%
“…The classic macroscopic Hill model, consisting of simple first order ordinary differential equations, is sufficient to simulate contracting muscle when considering hysteresis effects and has been firmly established as a reliable model of muscle contractile dynamics for many decades. A review of the developments of the Hill model up to 2016 can be found in [Ovesy, et al, 2016]. One of the major disadvantages of the Hilltype models is that the viscoelastic analogies do not map to the underlying physiological mechanisms associated with muscle.…”
Section: Results Of the Mathematical Modelmentioning
confidence: 99%
“…Ovesy et al [50] showed the λ model had a more realistic response rate compared to the Hill-type model. In a study of orofacial gestures, no clear biomechanical differences were found between the two models [47].…”
Section: Facial Muscle Modellingmentioning
confidence: 99%